The Effect of Mother’s Perfectism on Studying in Talents High Schools Girl's Mental Health and Social Commitment in Kerman City - soodeh maghsoudi; zahra sharifi (توسعه اجتماعی)
The objective of the present study is sociological investigation investigation of the effect of mother's perfectionism on mental health and social commitment of the girls studying in exceptional talents high schools in Kerman. Research method was survey and it was used perfectionism questionnaire by Hill et al. (2004), SCL-25, and social commitment by self-administered questionnaire statistical samples, based on the Cockheran sampling formula was 208 mothers and their daughters. The results showed a significant correlation between mother's perfectionism and mental health and social commitment of their daughters. It means that it is preditable mental health and social commitment of the girls by mother’s perfectism. Actually by increasing of mother’s perfectism it will decrease daughter’s mental health but it will increase social commitment.